2001
DOI: 10.1016/s0896-6273(01)00295-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Visualization of Local Protein Synthesis in Hippocampal Neurons

Abstract: Using pharmacological approaches, several recent studies suggest that local protein synthesis is required for synaptic plasticity. Convincing demonstrations of bona fide dendritic protein synthesis in mammalian neurons are rare, however. We developed a protein synthesis reporter in which the coding sequence of green fluorescent protein is flanked by the 5' and 3' untranslated regions from CAMKII-alpha, conferring both dendritic mRNA localization and translational regulation. In cultured hippocampal neurons, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
504
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 548 publications
(531 citation statements)
references
References 42 publications
24
504
0
3
Order By: Relevance
“…3A.2). Interestingly, they observed that the fluorescently labeled Kv1.1 was concentrated in stationary "hotspots" in dendrites similar to what was reported with other locally translated protein (Aakalu et al 2001).…”
Section: Single-cell Imagingsupporting
confidence: 79%
See 1 more Smart Citation
“…3A.2). Interestingly, they observed that the fluorescently labeled Kv1.1 was concentrated in stationary "hotspots" in dendrites similar to what was reported with other locally translated protein (Aakalu et al 2001).…”
Section: Single-cell Imagingsupporting
confidence: 79%
“…Schuman and colleagues created a dendritic translation reporter by flanking the coding sequence for GFP with the 5 0 and 3 0 untranslated regions (UTR) of the a subunit of Ca 2þ /calmodulindependent kinase II (aCaMKII) (Fig. 3A.1) (Aakalu et al 2001;Sutton et al 2004). The 3 0 UTR of aCaMKII has been shown to be sufficient for dendritic localization of the mRNA in neurons.…”
Section: Fluorescent Protein Reportersmentioning
confidence: 99%
“…Indeed, electron and confocal microscopy experiments indicate that local protein synthesis could be even restricted to individual synaptic spines (Aakalu et al, 2001;Ostroff et al, 2002). Furthermore, the transient activation of local protein synthesis is a particularly well-suited mechanism for coupling tagging with de novo transcription at the cell nucleus.…”
Section: B Regulation Of Local Protein Synthesismentioning
confidence: 99%
“…An elegant study using the arsenic-based dyes FlAsH and ReAsH showed that transfected tagged GluR1 and GluR2 subunits can be synthesized in a dendritic compartment independent from the cell body, in cultured hippocampal neurons (Ju et al, 2004). Studies using a protein synthesis reporter consisting of GFP flanked by the 5= and 3= untranslated regions from the CaMKII ␣-subunit, which contains information sufficient for the dendritic localization of the mRNA, also showed that BDNF may induce dendritic protein synthesis (Aakalu et al, 2001). The neurotrophin BDNF plays an important role in synaptic plasticity (Carvalho et al, 2008), and studies in hyppocampal synaptoneurosomes showed that BDNF induces local synthesis of GluR1 (Schratt et al, 2004).…”
Section: Role Of Ampars In Ltpmentioning
confidence: 99%